Impact of Hearing Aid Use on Falls and Falls-Related Injury: Results From the Health and Retirement Study. Issue 2 (29th March 2022) - Riska, Kristal M.; Peskoe, Sarah B.; Kuchibhatla, Maragatha; Gordee, Alexander; Pavon, Juliessa M.; Kim, Se Eun; West, Jessica S.; Smith, Sherri L.
Abstract : Objectives: Falls are considered a significant public health issue and falls risk increases with age. There are many age-related physiologic changes that occur that increase postural instability and the risk for falls (i.e., age-related sensory declines in vision, vestibular, somatosensation, age-related orthopedic changes, and polypharmacy). Hearing loss has been shown to be an independent risk factor for falls. The primary objective of this study was to determine if hearing aid use modified (reduced) the association between self-reported hearing status and falls or falls-related injury. We hypothesized that hearing aid use would reduce the impact of hearing loss on the odds of falling and falls-related injury. If hearing aid users have reduced odds of falling compared with nonhearing aid users, then that would have an important implications for falls prevention healthcare. Design: Data were drawn from the 2004-2016 surveys of the Health and Retirement Study (HRS). A generalized estimating equation approach was used to fit logistic regression models to determine whether or not hearing aid use modifies the odds of falling and falls injury associated with self-reported hearing status. Results: A total of 17, 923 individuals were grouped based on a self-reported history of falls. Self-reported hearing status was significantly associated with odds of falling and with falls-related injury when controlling for demographic factors and important health characteristics. Hearing aid use was included as an interaction in the fully-adjusted models and the results showed that there was no difference in the association between hearing aid users and nonusers for either falls or falls-related injury. Conclusions: The results of the present study show that when examining self-reported hearing status in a longitudinal sample, hearing aid use does not impact the association between self-reported hearing status and the odds of falls or falls-related injury.